Religion, Culture, and Education in Development, Reading Soedjatmoko's Perspective: A Preliminary Note - Ayu Ambarwati (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This article explains Soedjatmoko's view on the role of religion, culture and education in human development in Indonesia. The role of religion and culture and education in various changes and challenges of the times can be read from the perspective of individual personal interests and the interests of society. The problem is, in its purpose and method, the two functions are not always compatible and even contradictory. For in achieving personal perfection a religious person can focus his life and practice on a personal and direct relationship with God, and become indifferent to his society. That is why, Soedjatmoko also emphasized the importance of the social function of religion and culture to strengthen belief in relation to the development of education towards the future. In this case, religion, culture and education can mutually enrich the civilization of the Indonesian people as long as the constructive and positive values in them can be utilized for humanity, civility and mutual progress.